D-shape Optical Fiber Development and Enhancement as a Refractive Indices Sensor Using Surface Plasmon Resonance - Hiba Kh. Abbas*; Zainab F. Mahdi (Iraqi Journal of Laser, 2023)
This article showcases the development and utilization of a side-polished fiber optic sensor that can identify altered refractive index levels within a glucose solution through the investigation of the surface Plasmon resonance (SPR) effect. The aim was to enhance efficiency by means of the placement of a 50 nm-thick layer of gold at the D-shape fiber sensing area. The detector was fabricated by utilizing a silica optical fiber (SOF), which underwent a cladding stripping process that resulted in three distinct lengths, followed by a polishing method to remove a portion of the fiber diameter and produce a cross-sectional D-shape. During experimentation with glucose solution, the side-polished fiber optic sensor revealed an adept detection sensitivity of 0.2015 au. /RIU. In order to improve sensitivity, a recent sensor was subjected to a coating process utilizing a thin film layer of gold (Au) measuring a thickness of 50 nm. The sensor was subsequently subjected to a series of tests utilizing the same glucose solutions as in previous experiments. A notable enhancement in sensitivity was observed when utilizing gold as the sensing material, with an equivalent maximum sensitivity of 3.101 au. /RIU.